Transposon mutagenesis in RT 078 Clostridioides difficile - te Vrugt, Marcel (2023)
Clostridioides difficile is a Gram-positive, spore-forming, anaerobic bacterium and a major cause of healthcare associated diarrhoea. Significant increases in the incidence of hypervirulent strains, such as those belonging to PCR ribotype (RT) 027, and increased antibiotic resistance have formed the focus of current C. difficile clinical research. Hypervirulent strains belonging to RT 078, in contrast, have received comparative less attention, despite the fact that they are widely recognized as being zoonotic, with a particular association with pigs. A greater understanding of RT 078 strains would benefit from the implementation of forward genetic approaches. Here we sought to implement Transposon directed insertion-site sequencing (TraDIS), a high throughput method able to define gene essentiality under niche-specific conditions, to elucidate physiological changes such as sporulation and germination in RT 078 strains. As effective DNA transfer is a prerequisite for TraDIS implementation, the most efficient strains as both donor and recipient in conjugation were identified. Applying next generation sequencing technologies on 10 clinical isolates and subsequent methylome analysis demonstrated that although the tested strains of RT 078 were genetically similar (up to 99.99%), they possess a variety of potential Restriction-Modification (R-M) barriers. One of these R-M systems was circumvented using the novel Escherichia coli donor strain, sExpress. Improved DNA transformability in C. difficile RT 078 strain CD9301 made it an optimal target for further genetic manipulations and subsequent TraDIS analysis. Subsequently, several transposon delivery systems were evaluated, based on their potential to mediate random transposon insertion and reliable plasmid loss, to prevent interference of the transposase during downstream experiments in C. difficile. The Tet-inducible transposon vector pRF215, performed best in CD9301. Based on this plasmid system, the novel vector pMTL-MtV10 was created, which was additionally equipped with I-SceI digestion sites, to achieve increased plasmid clearance during library preparation. Using both plasmids, genes essential for growth in rich media were determined. In total, 448 essential genes were predicted. The incorporation of I-SceI sites into pMtV-10 did not, however, improves plasmid loss during the TraDIS library preparation. A further 398 genes were predicted to be essential for sporulation. The number of genes identified is most likely an underestimate as the manual cut-off used to predict essentiality lacks sensitivity. The described findings lay the ground work necessary for determining essentiality in RT 078 and improving our understanding of this important ribotype.